WebGIS Utilization for Information Dissemination of Indonesia Outer Small Islands - M T Al Asy’ari; M F Muhyidin; A Poniman; M Supriyatno (Proceeding International Conference on Information Technology and Business, 2019)
Indonesia is a country that has an area of 1.9 million km2 with a total of 16,056 islands. The realization of Indonesia as an archipelagic country can be achieved by optimally and effectively utilizing the territorial wealth of Indonesia which is the capital and common property of the Indonesian people. As an archipelago, Indonesia must be able to maintain national security by safeguarding its territory and securing existing maritime resources. This research shows how to use webGIS using Google Earth web version, Google My Maps, and ArcGIS Online to disseminate information on Indonesia's outer small islands. From the results of the study, obtained information on the name of the island, another name of the island, waters, coordinates of the outer point of the island, administrative data, neighboring countries, and population. WebGIS that has been made requires additional data in the form of resolution satellite imagery to identify outermost small islands that are not clearly visible. With the dissemination of information on the outer small islands, it can help policymakers in the development of the outer small islands can be done by paying attention to aspects of defense and security.Keywords: webGIS, Indonesia outer small islands, Google Earth web version, ArcGIS Online